Climate Change and the CO₂ Emissions Mitigation Action Plan in the Municipality of Campinas/SP - Bottoni, Irineu José; Normanha, Bruno de Aguiar; Sugahara, Cibele Roberta; Ferreira, Denise Helena Lombardo; Silva , Marcelo Pereira da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – This article analyzes how the CO₂ emission reduction targets of the Campinas/SP Local Climate Action Plan (PLAC) can align with the Municipal Policy to Address the Impacts of Climate Change in CampinasMethodology – The research method adopted is qualitative, descriptive, and documentary.Originality/Relevance – The relevance of the article lies in examining GHG emissions in the municipality of Campinas, focusing on the necessary transitions identified in its policies and plans to combat the climate crisis to make the municipality more sustainable, inclusive and resilient.Results – Scientific evidence shows that global warming is already advanced, driven by human activities that emit Greenhouse Gases (GHG). Even if future emissions are drastically reduced, the effects of past emissions will continue to impact the global climate for decades. This makes it urgent not only to reduce emissions, but also to adopt adaptation and mitigation measures to minimize the impacts of ongoing climate change.Theoretical Contributions – The study concludes that cities that control their emissions, with short, medium, and long-term visions and actions to address climate crises, with measurable, reportable, and verifiable goals, and innovative solutions, are better prepared to face extreme weather events, such as floods, droughts, and heatwaves, which tend to intensify due to global warming.Social and Environmental Contributions – Greenhouse Gas (GHG) emissions are identified as the main drivers of climate change. Cities and industries are the major GHG emitters, and the population bears the consequences. Mitigating climate change and adapting to its effects are central issues in public policy formulation at all levels — national, state, and local.
Keywords: Greenhouse Gas Emissions (GHG); Climate Change; Sustainability